An ANSYS/LS-DYNA Simulation and Experimental Study of Sectional Hob Type Laver Harvesting Device - Jiahong Tang; Xiuchen Li; Guochen Zhang; Wei Lu; Shang Ni; Zhenyin Sun; Haidong Li; Cheng Zhao; Hanbing Zhang; Qian Zhang; Gang Mu (Agriculture, 2023)
To solve the problems of low net harvesting rate, high loss rate, and uneven stubble height during the harvest of laver, the laver (Porphyra yezoensis) was selected as the research object, the analysis of the cultivation mode, biomechanical characteristics, harvesting trajectory and force of laver were carried out. A sectional hob type harvesting device was designed. A rigid-flexible coupling model related to the interaction between the cutting mechanism and the laver was constructed based on ANSYS/LS-DYNA. The Box–Behnken design method was used to simulate the effects of different structural parameters and process parameters on the force of laver cutting, and the bench test of the laver harvesting device was carried out. The simulation results showed that the four factors that significantly affect the force exerted on the laver during cutting in proper order were cutter revolving speed, knife extension length, knife inclination angle and forward velocity. When the combination of the forward velocity, the cutter revolving speed, the knife extension length and inclination angle was 0.77 m/s, 900 r/min, 40 mm, and 110°, respectively, the cutting force on laver was the smallest, which was 4.21 N. The bench test of harvesting performance showed that the cutter revolving speed has a significant impact on the recovery rate, and the forward velocity has a significant impact on the loss rate. When the harvesting speed ratio was λ4 (the cutter revolving speed was 900 r/min and the forward velocity was 0.77 m/s), the net harvesting rate and the loss rate were 97.45% and 3.38%, respectively, and the cutting proportion of laver can reach 77.5%. The results of the study provide a theoretical basis for the development of harvesting for laver.